Umayyad Poetry as Viewed by Critics: Artistic Imagery as a Criterion Of Comparison between Poets as a model - sija jasim muhamad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The summary is characterized by the umayyad era the activity of intellectual movement that marched in different directions، including the field of poetic production، the era witnessed the emergence of different trends of poetry varied by the diversity of the hair environments of Hijaz، Sham، And Iraq، and resulted in the emergence of various purposes of poetry of praise and satire ، and inheritance And yarn، pride، as well as the art of extremes that has developed remarkable in this era. This poetic activity was accompanied by a critical movement whose owners distinguishbetween the arts of saying and interpreting and describing and monitoring to issue their monetary judgments، the poetic product was a fertile material for literary criticism in the Umayyad era and the following times، and our research came to look at the Umayyad poetic texts that were criticized for the statement of the foundations Adopted by critics in issuing critical judgment، we chose artistic photography as a criterion for trade-off in the critical judgment of selected Umayyad poeticModels.